The Effect of Digital Technology and Agility On Company Performance with Management Accounting System as Mediation - W A Astuti; Y Augustine (Universitas Komputer Indonesia, 2022)
The aim of this research was to look into and evaluate the impact of digital technology and agility with management accounting information systems as a mediating variable. The research method used is descriptive analysis and verification. By distributing questionnaires addressed to directors / managers / heads of company divisions. The results showed that digital technology and agility mediated Accounting information systems used by management have a positive impact on organization success. Based on the structural model's assessment, digital technology and accounting information system for management agility have a better strong outcome than the direct effect with a value of 85%. accounting information system for management are required to get over uncertainty in deciding and evaluating the causal relationship that occurs due to digital technology that continues to develop in the millennial era with the agility that companies need. The contribution of research so that companies continue to innovate with changing technological developments and a manager's agility is crucial in decision making.